People at work [2] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Special Paper in CTA s Annual Report 2001, by Betty Wampfler discusses Achievements, limits and prospects of microfinance as a means of financing agricultural and rural development: the experience in West Africa'.